PRÁTICAS SUSTENTÁVEIS PARA LEGITIMAÇÃO ORGANIZACIONAL NO TERRITÓRIO: A OPÇÃO ENTRE A PERSPECTIVA DA ECONOMIA AMBIENTAL OU DA ECONOMIA ECOLÓGICA /SUSTAINABLE PRACTICES FOR ORGANIZATIONAL LEGITIMATION IN THE TERRITORY: THE CHOICE BETWEEN THE ENVIRONMENTAL ECONOMY OR THE ECOLOGICAL ECONOMY PERSPECTIVE - Wbatuba, Berenice; Silveira, Daniel; Deponti, Cidonea; Arend, Silvio Cezar (Informe GEPEC, 2022)
As organizações tem adotado um novo estilo de gestão e divulgação de suas práticas sustentáveis para seus públicos de interesse, combinando eficiência econômica, responsabilidade social e ambiental, para serem percebidas como legítimas na sociedade. O objetivo da pesquisa foi analisar como duas empresas de grande porte do COREDE Missões/RS divulgam as práticas sustentáveis adotadas, sob as perspectivas das Economias Ambiental e Ecológica. Ambas desenvolvem medidas de prevenção e recuperação ambiental, por exigência legal, do mercado ou por gestão estratégica, caracterizando assim noção do contrato social existente entre as empresas e a sociedade. Os achados da pesquisa evidenciam uma preocupação com o meio ambiente muito mais voltada ao desenvolvimento sustentável do modelo tipicamente capitalista, hegemônico, antropocêntrico do que no sentido contrário, do ecodesenvolvimento e a divulgação aos stakeholders reforça muito mais o caráter de marketing institucional de cumprimento às normas e leis impostas do que a efetiva consciência de sustentabilidade ambiental. Abstract: Organizations had adopted a new style of management and disclosure of their sustainable practices with their stakeholders, one that combines economic efficiency, social and environmental responsibility, so that they are perceived as legitimate in society. The research objective was to analyze how two large companies in COREDE Missões/RS are disclosing the sustainable practices adopted in order, under the perspectives of Environmental Economics or Ecological Economics. Both develop measures of environmental prevention and recovery, by legal requirement, market or strategic management, thus characterizing the notion of the existing social contract between companies and society. The research findings show a concern with the environment that is much more focused on sustainable development of the typically capitalist, hegemonic, anthropocentric model, than in the opposite direction, of ecodevelopment and the disclosure to stakeholders reinforces much more the character of institutional marketing of compliance with imposed norms and laws than the effective awareness of environmental sustainability.